Response surface methodology for controlling the release of anthocyanin from sago starch films - Che Hamzah, Nurul Husna; Khairuddin, Nozieana; Muhamad, Ida Idayu; Sarbini, Shahrul Razid (Springer, 2024)
The use of anthocyanin as a natural colorant in the food industry has been widely established because it is non-toxic. Because of that, the role of this colorant is expanding to food packaging as intelligent packaging is now becoming the trend for urban lifestyles. In this study, biodegradable packaging from starch-based film incorporated with Brassica oleracea anthocyanin was developed by casting technique. The research focused on optimization strategies, utilizing Response Surface Methodology (RSM) to examine how the concentration of anthocyanin in films, along with buffer pH, temperature, and contact time variables, affect total color difference (TCD) and absorbance values, which are indicative of anthocyanin release. The experiments were designed using a Box-Behnken Design (BBD) by applying 29 full factorial designs with five center points. The collected experimental data were used to fit a second-order polynomial equation through multiple regression analysis and were then analyzed using suitable statistical techniques. By utilizing 3-D response surface and contour plots generated from mathematical models, the optimal conditions were identified. The optimum formulation of this anthocyanin incorporated in sago starch films was as follows: anthocyanin concentration 8.2 g, pH of buffer solution 7.9, surrounding temperature 4.1°C, and contact time 35.8 minutes. Under these conditions, the films’ reaction produced the highest color difference and lowest absorbance which were 5.7 and 0.0004 respectively. This outcome demonstrates that optimization methods can reduce the release of anthocyanins from starch films, highlighting a significant color variation that enhances its suitability for advanced food packaging purposes.